46 The impact of in situ simulation on clinical practice. (22nd November 2019) - Simpson, Gabrielle; Ross, Alasdair; Broughton, Emma; Adair, Eddie
Abstract : Introduction: Through facilitating in situ simulation, we aim to improve non technical skills i.e. team work & communication. Providing a learning environment within the candidates' clinical area allows a higher depth of immersion throughout the scenario. Enabling us to deliver focused rehearsal and to reach a wider audience; in situ Simulation aims to enhance patient safety by improving clinical performance and systems safety. Method: We have developed programmes that are tailored to the clinical areas specific needs through an individualised educational needs assessment process. This has enabled us to create a personalised curriculum for each area to address local safety issues and provide continuity and quality assurance. In situ sessions are delivered from weekly to monthly depending on clinical requirement. Following the simulation scenario, we use a standardised debriefing tool that focuses on exploring human factors with the scope to cover knowledge or performance gaps where necessary. Results: As a team of simulation educators we have reached out to 36 clinical areas which is greater than 90% of the hospital. We have delivered in situ simulation to 1018 candidates over the past 12 months and sessions have been evaluated at 4.6/5 for overall usefulness. Evaluation themes around impact on practice have included; confidence building, team work development and the use of closed loop communication tools. The evaluations have also demonstrated the need for this programme. Conclusion: Increasing the in situ simulation provision for the clinical areas has enhanced practice through the development of the non technical skills required to deliver safe and effective patient care. Feedback suggests a positive impact on the multidisciplinary team and has demonstrated improved confidence in practice for many of the participants. The use of a specifically tailored curriculum which is clinically relevant to the candidates has also ensured a high level of engagement from staff.